Cannabinoids and cannabinoid-like compounds: Biochemical characterization and pharmacological perspectives - Oksana Yu. Kytikova; Yulia K. Denisenko; Tatyana P. Novgorodtseva; Ivan S. Kovalenko (Russian Open Medical Journal)
Publication interest in cannabinoids, including phytocannabinoids, endogenous cannabinoids, synthetic cannabinoids and cannabinomimetic compounds, is due to the therapeutic potential of these compounds in inflammatory pathology. Since recent years, scientific interest was focused on compounds with cannabinomimetic activity. The therapeutic use of phytocannabinoids and endocannabinoids is somewhat limited due to unresolved issues of dosing, toxicity and safety in humans, while cannabinoid-like compounds combine similar therapeutic effects with a high confirmed safety. Targets for endocannabinoids and phytocannabinoids are endocannabinoid receptors 1 and 2, G protein-coupled receptors (GPCRs), peroxisome proliferator-activated receptors (PPARs), and transient receptor potential ion channels (TRPs). Non-endocannabinoid N-acylethanolamines do not interact with cannabinoid receptors and exhibit agonist activity towards non-cannabinoid receptors, such as PPARs, GPCRs and TRPs. This literature review includes contemporary information on the biological activity, metabolism and pharmacological properties of cannabinoids and cannabinoid-like compounds, as well as their receptors. We established that only a few studies were devoted to the relationship of non-endocannabinoid N-acylethanolamines with non-cannabinoid receptors, such as PPARs, GPCRs, and also with TRPs. We have focused on issues that were insufficiently covered in the published sources in order to identify gaps in existing knowledge and determine the prospects for scientific research.